Design and construct a smart xenon flashlamp driver - Tamuri, Abd. Rahman; Bidin, Noriah; Mat Daud, Yaacob (2006)
Flashlamp is an optical pumping source for Nd:YAG laser. The aim of this project is to design and construct a driver for xenon flashlamp. The design composed of four main circuits that are: simmer supply, discharge capacitor, control unit and ignition circuit. Initially, the driver was feed in with a pulse of 1.5 Ã¬s and 3.68 V to open the gate of SCR. The pulse then induced a giant pulse of 4.34 kV and 5 Ã¬s to ignite and cause pre-breakdown in the flashlamp. A voltage between electrodes was formed drop to 120 V and maintain current of 120 mA. Discharge capacitor circuit was triggered flashlamp with 600 V and the peak current of 149 A. Brilliance white lights have been flashed and produced broad band spectra with majority at 823 nm.